Comparative study of spinning field development in two species of araneophagic spiders (Araneae, Mimetidae, Australomimetus) - Mark A. Townley; Danilo Harms (Evolutionary Systematics, 2017)
External studies of spider spinning fields allow us to make inferences about internal silk gland biology, including what happens to silk glands when the spider molts. Such studies often focus on adults, but juveniles can provide additional insight on spinning apparatus development and character polarity. Here we document and describe spinning fields at all stadia in two species of pirate spider (Mimetidae: Australomimetus spinosus, A. djuka). Pirate spiders nest within the ecribellate orb-building spiders (Araneoidea), but are vagrant, araneophagic members that do not build prey-capture webs. Correspondingly, they lack aggregate and flagelliform silk glands (AG, FL), specialized for forming prey-capture lines in araneoid orb webs. However, occasional possible vestiges of an AG or FL spigot, as observed in one juvenile A. spinosus specimen, are consistent with secondary loss of AG and FL. By comparing spigots from one stadium to tartipores from the next stadium, silk glands can be divided into those that are tartipore-accommodated (T-A), and thus functional during proecdysis, and those that are not (non-T-A). Though evidence was more extensive in A. spinosus, it was likely true for both species that the number of non-T-A piriform silk glands (PI) was constant (two pairs) through all stadia, while numbers of T-A PI rose incrementally. The two species differed in that A. spinosus had T-A minor ampullate and aciniform silk glands (MiA, AC) that were absent in A. djuka. First instars of A. djuka, however, appeared to retain vestiges of T-A MiA spigots, consistent with a plesiomorphic state in which T-A MiA (called secondary MiA) are present. T-A AC have not previously been observed in Australomimetus and the arrangement of their spigots on posterior lateral spinnerets was unlike that seen thus far in other mimetid genera. Though new AC and T-A PI apparently form throughout much of a spider’s ontogeny, recurring spigot/tartipore arrangements indicated that AC and PI, after functioning during one stadium, were used again in each subsequent stadium (if non-T-A) or in alternate subsequent stadia (if T-A). In A. spinosus, sexual and geographic dimorphisms involving AC were noted. Cylindrical silk gland (CY) spigots were observed in mid-to-late juvenile, as well as adult, females of both species. Their use in juveniles, however, should not be assumed and only adult CY spigots had wide openings typical of mimetids. Neither species exhibited two pairs of modified PI spigots present in some adult male mimetids.